Geometric, electronic and transport properties of bulged graphene: A theoretical study - Ling, Faling; Liao, Rui; Yuan, Chao; Shi, Xiaowen; Li, Li; Zhou, Xianju; Tang, Xiao; Jing, Chuan; Wang, Yongjie; Jiang, Sha (The Journal of chemical physics, 2023)
Out-of-plane deformation in graphene is unavoidable during both synthesis and transfer procedures due to its special flexibility, which distorts the lattice and eventually imposes crucial effects on the physical features of graphene. Nowadays, however, little is known about this phenomenon, especially for zero-dimensional bulges formed in graphene. In this work, employing first-principles-based theoretical calculations, we systematically studied the bulge effect on the geometric, electronic, and transport properties of graphene. We demonstrate that the bulge formation can introduce mechanical strains (lower than 2%) to the graphene’s lattice, which leads to a significant charge redistribution throughout the structure. More interestingly, a visible energy band splitting was observed with the occurrence of zero-dimensional bulges in graphene, which can be attributed to the interlayer coupling that stems from the bulged structure. In addition, it finds that the formed bulges in graphene increase the electron states near the Fermi level, which may account for the enhanced carrier concentration. However, the lowered carrier mobility and growing phonon scattering caused by the formed bulges diminish the transport of both electrons and heat in graphene. Finally, we indicate that bulges arising in graphene increase the possibility of intrinsic defect formation. Our work will evoke attention to the out-of-plane deformation in 2D materials and provide new light to tune their physical properties in the future.